(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The current research aims to identify the impact of using the daily to-do list method, based on the 21-day theory, on forming and enhancing healthy habits in the fitness and health culture subject at the secondary level. The research was applied to a sample of (47) female students from the second secondary grade at the second secondary school in the Makkah Al-Mukarramah region for the academic year 1446 AH - 2024 AD. The research sample was divided into two groups: the experimental group, comprising (25) students, and the control group, comprising (22) students. To achieve the research objectives, a pre- and post-questionnaire was used, along with daily to-do lists to track progress. The validity of the questionnaire was verified using appropriate methods. The research results revealed statistically significant differences between the average responses of the students in the post-questionnaire in favor of the experimental group. This was attributed to the use of the daily to-do list method, based on the 21-day theory, to form habits. This contributed to increasing self-awareness among the students and enhancing their organizational and health behaviors. The study made several recommendations, including encouraging teachers to use daily to-do lists as an educational tool and strategy for building habits or skills in academic subjects and training them on them.